Bismuth metal negative electrode, preparation thereof and application of bismuth metal negative electrode in sodium ion battery
Through magnetron sputtering technology, the composite of bismuth metal layer on the current collector substrate has solved the problem of complex and high cost in the preparation process of existing bismuth negative electrode materials, and the efficient embedding and deintercalation of bismuth negative electrode materials in sodium ion batteries is achieved, and the adaptability of bismuth negative electrode materials is achieved. High surface load positive electrode and high current applications.
Patent Information
- Application Number
- CN202411468805.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The preparation process of existing bismuth negative electrode materials is complex and the conditions are strict, and bismuth powder needs to be pretreated to suppress volume expansion, which increases the cycle life requirement, which is not conducive to processing and cost control.
Magneto-controlled sputtering technology is used to composite bismuth metal layer on the current collector substrate, and the sodium ion embedding and deintercalation efficiency and stability are improved through multi-stage sputtering and optimization of sputtering parameters.
The bismuth negative electrode material adapted to sodium ion batteries is realized, which improves the efficiency and stability of sodium ion insertion and deintercalation, and adapts to the application requirements of high-plane load positive electrodes and high currents.
Smart Images

Figure CN119447196A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular to the technical field of sodium ion battery electrodes. Technical Background
[0002] In recent years, sodium-ion batteries have attracted widespread attention as a substitute for lithium-ion batteries. In addition to traditional carbon-based negative electrode materials, alloyed negative electrode materials are considered to be one of the excellent candidates for the new generation of high energy density / power density sodium-ion battery negative electrode materials due to their high theoretical specific capacity and suitable voltage platform. For example, metals such as bismuth, tin, antimony, and lead can all be used to store sodium by alloying with sodium. Among them, bismuth metal has low toxicity, is environmentally friendly, has abundant reserves, and has a high theoretical capacity and exhibits a suitable sodiumization voltage (average 0.55V (vs. Na + / Na)), and the layered structure of bismuth with a large interlayer spacing makes its volume expansion relatively smaller during the sodium insertion / extraction process, making it a very promising negative electrode material.
[0003] However, the prior art mainly prepares bismuth negative electrodes by electroplating or coating a mixture of bismuth powder and a binder on a current collector and other traditional electrode sheet preparation methods. For example, Chinese patent document with publication number CN116435495A discloses a bismuth electrode material, which specifically records that a bismuth compound is obtained by electrochemical reduction. Chinese patent document with publication number CN113140723A discloses a coated wide-temperature sodium ion battery based on a metallic bismuth negative electrode.
[0004] In summary, the existing bismuth negative electrode material preparation process is complex and the conditions are strict. At the same time, bismuth powder generally needs to be pretreated to inhibit its volume expansion, thereby increasing the cycle life of the bismuth negative electrode, which is not conducive to processing and cost control. Therefore, in order to avoid the above problems, it is necessary to develop a simpler and more efficient bismuth negative electrode production method. Summary of the invention
[0005] In order to solve the application performance of bismuth metal negative electrode in sodium metal battery, the first purpose of the present invention is to provide a method for preparing bismuth metal negative electrode for sodium ion battery, aiming to improve its application performance in sodium ion battery.
[0006] The second purpose of the present invention is to provide a bismuth metal negative electrode prepared by the preparation method and its application in a sodium ion battery.
[0007] The third object of the present invention is to provide a sodium ion battery comprising the bismuth metal negative electrode.
[0008] A method for preparing a bismuth metal negative electrode comprises sputtering a bismuth metal active layer on a current collector substrate by magnetron sputtering to prepare the bismuth metal negative electrode.
[0009] Different battery systems have different requirements for electrodes. For example, for lithium-ion and sodium-ion batteries, the radius of sodium ions is larger than that of lithium ions, and materials adapted to lithium-ion batteries are difficult to directly convert and adapt to sodium-ion battery applications. For example, for batteries with negative electrodes and batteries without negative electrodes, the behavior of active ions in the electrodes is also different, and they also need to face different problems. For example, for the negative electrode of a sodium-ion battery, compared with a battery without a negative electrode, it needs to withstand the many problems caused by the frequent embedding and de-embedding of sodium ions. The topic shifts to the present invention. In response to the problems with bismuth-containing negative electrodes, the present invention attempts to provide a negative electrode material in the industry that directly composites a metal bismuth layer on a current collector. However, studies have found that when such materials are used as negative electrodes for sodium-ion batteries, they need to solve the problems of large sodium ion embedding and de-embedding impedance, and easy expansion, powdering and peeling. In response to the problems faced by this idea, the present invention innovatively uses ion sputtering to compound bismuth metal particles on the current collector, which helps to prepare a bismuth negative electrode that is suitable for sodium ion batteries and has excellent sodium ion embedding and de-embedding efficiency and stability; not only that, it can also unexpectedly adapt to the application requirements of high surface load positive electrode and large current.
[0010] In the present invention, there is no special requirement for the current collector substrate, and any current collector with conductivity suitable for sodium ion batteries can be selected. For example, the current collector substrate can be at least one of aluminum foil, carbon-coated aluminum foil, and copper foil.
[0011] In the present invention, the metal bismuth composite layer is constructed on the current collector substrate based on the sputtering method, and the key to improving the efficiency, path and stability of sodium ion embedding and de-embedding is to be found. On this basis, the study also found that further optimizing and controlling the parameters and methods of sputtering can help to unexpectedly further construct the physical and chemical structure and stability that are compatible with sodium ion embedding and de-embedding, thereby helping to further improve the performance of the prepared bismuth metal negative electrode.
[0012] In the present invention, the magnetron sputtering stage adopts a direct current power supply for sputtering.
[0013] In the present invention, the initial vacuum degree of sputtering is 1×10 -6 ~1×10 -4 Pa, preferably, the initial vacuum degree is 3×10 -6 ~4×10 -5 Pa, further 7×10 -6 ~1×10 -5 Pa.
[0014] In the present invention, the flow rate of argon gas during the sputtering process is 20 to 150 sccm, preferably, the flow rate of argon gas is 50 to 120 sccm, and further preferably, 80 to 110 sccm.
[0015] In the present invention, the sputtering power is 10 to 80 W, preferably, the sputtering power is 20 to 65 W, and more preferably, 25 to 55 W.
[0016] In the present invention, the total sputtering time is 5 to 120 min, preferably 5 to 90 min, and more preferably 30 to 70 min.
[0017] In the present invention, the sputtering process includes N sputtering processes, wherein adjacent sputtering stages are separated by a time interval of t, and the pressure of the system during the interval is negative pressure; N is 2 to 6; the time t is within 5 minutes; and the time of each sputtering stage is 0.1 to 2 times the average sputtering time.
[0018] The research of the present invention also shows that the innovative use of the multi-stage sputtering method, combined with the processing parameters such as the vacuum interval, can further optimize the distribution behavior and interface structure of metal bismuth on the current collector substrate, and can further optimize the efficiency and path of sodium ion embedding and de-embedding, which helps to further enhance its performance under high surface load positive electrode and high current.
[0019] In the present invention, N is 2 to 3; the time t is 1 to 5 minutes; the time of each sputtering stage is 0.5 to 1.5 times, and further 0.5 to 1 times, of the average sputtering time.
[0020] For example, in a preferred embodiment of the present invention, bismuth metal is used as a target material and a current collector substrate is used as a substrate for magnetron sputtering, wherein the magnetron sputtering includes a first stage of magnetron sputtering, followed by a second stage of magnetron sputtering after a period of time (t) under vacuum. In a further preferred embodiment, after the second stage of magnetron sputtering, a third stage of magnetron sputtering is performed after a period of time under vacuum.
[0021] Preferably, during the N-stage sputtering process, the power of the N-stage sputtering is 0.5 to 1 times the power of the N-1-stage sputtering. Preferably, during the N-stage sputtering process, the time of the N-stage sputtering is 0.1 to 1 times the time of the N-1-stage sputtering. The present invention also shows that the gradient control of the power and time of the multi-stage sputtering stage can further optimize the occurrence structure of the bismuth metal layer, which helps to further improve the stability of the prepared high-surface-load positive electrode and high current.
[0022] For example, the N-stage sputtering process is a two-stage sputtering process, wherein the power of the first stage magnetron sputtering is 25-35W, and the time of the first stage magnetron sputtering is 15-25Min; the power of the second stage magnetron sputtering is 20-30W, and the time of the second stage magnetron sputtering is 15-25Min; further preferably, the power of the first stage magnetron sputtering is 25-35W, and the time of the first stage magnetron sputtering is 20-25Min; the power of the second stage magnetron sputtering is 20-25W, and the time of the second stage magnetron sputtering is 20-25Min. The present invention shows that under the preferred conditions, sputtering mechanism and conditions, better synergistic performance can be obtained.
[0023] The present invention preferably adopts a three-stage sputtering process, wherein the power of each sputtering stage can be 25 to 35 W, wherein the sputtering time of the first two stages is 20 to 25 minutes, and the sputtering time of the last stage is 10 to 25 minutes (preferably 10 to 15 minutes).
[0024] The invention also provides a bismuth metal negative electrode prepared by the preparation method.
[0025] In the present invention, the preparation method can give the prepared material special physical and chemical characteristics, and the material with the characteristics prepared by the preparation method has more advantages in adaptability to high-surface-loaded positive electrodes, and can still obtain excellent electrochemical properties under large currents.
[0026] The bismuth metal negative electrode of the present invention has a bismuth metal layer with a loading capacity of 0.5-6 mg cm -2 ; furthermore, it can be considered as 2-4 mg cm -2 .
[0027] The present invention also provides an application of the bismuth metal negative electrode, which is used as a negative electrode for preparing a sodium ion battery.
[0028] The present invention innovatively uses the bismuth metal negative electrode as the negative electrode. Based on its physical and chemical characteristics, it can solve the problems of unsatisfactory embedding and de-embedding efficiency of sodium ions in the negative electrode, easy pulverization and peeling, and can improve its application performance in sodium ion batteries.
[0029] The present invention also provides a sodium ion battery, comprising a positive electrode, a barrier layer and a negative electrode which are composited in sequence, wherein the negative electrode is a bismuth metal negative electrode prepared by the preparation method of the present invention.
[0030] In the present invention, the sodium ion battery, except for the bismuth metal negative electrode of the present invention, can have known components and structures. In addition, the positive electrode of the present invention can be a conventional positive electrode, and further can be a conventional coated positive electrode. Furthermore, the surface loading of the positive electrode can be 2-27 mg cm -2; furthermore, it can be 10 to 20 mg cm -2 .
[0031] In the present invention, the barrier layer may be a diaphragm, or a solid or semi-solid electrolyte.
[0032] In addition, in the sodium ion battery, it is also allowed to add a conventional electrolyte as needed. For example, when the barrier layer is a non-solid electrolyte, it is allowed to add an electrolyte to the system.
[0033] Beneficial Effects
[0034] The present invention provides for the first time a bismuth metal negative electrode material having a bismuth metal layer directly composited on a current collector by sputtering, and finds that the material can unexpectedly adapt to the sodium ion embedding and de-embedding application requirements of the negative electrode of a sodium ion battery, and can improve the performance of the sodium ion battery. In addition, on this basis, the use of multi-stage sputtering and the optimal gradient control of the multi-stage sputtering power and time can further strengthen the physical and chemical structure of the prepared material, and can further improve the application performance of the prepared material in sodium ion batteries.
[0035] The research of the present invention shows that the bismuth metal negative electrode prepared by the preparation method can adapt to the application requirements of high surface loading positive electrode, so it can still show excellent embedding and de-embedding efficiency and stability under large current. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The SEM image of the bismuth negative electrode obtained in Example 1
[0037] Figure 2 This is the SEM image of the bismuth negative electrode obtained in Example 1 after 100 cycles of half-cell assembly according to the test conditions.
[0038] Figure 3 The room temperature cycle performance diagram of the half-cell assembled with the bismuth negative electrode prepared in Example 1
[0039] Figure 4 The room temperature rate performance diagram of the half-cell assembled with the bismuth negative electrode prepared in Example 1
[0040] Figure 5 The room temperature cycle performance diagram of the full battery assembled with the bismuth negative electrode prepared in Example 1
[0041] Figure 6 The room temperature cycle performance diagram of the half-cell assembled with the scraped bismuth negative electrode prepared in Comparative Example 3 Specific embodiments
[0042] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0043] An optional method for preparing a bismuth negative electrode by magnetron sputtering of the present invention comprises the following steps:
[0044] 1) Install the bismuth target and place the clean current collector flat on the sample holder of the magnetron sputtering equipment chamber;
[0045] 2) Turn on the magnetron sputtering equipment and adjust the equipment to the required coating process;
[0046] 3) Using single-stage or step-by-step sputtering, a certain amount of metallic bismuth is sputtered on the surface of the current collector to obtain a bismuth negative electrode.
[0047] The negative electrode substrate of the present invention is made of one of aluminum foil, carbon-coated aluminum foil and copper foil;
[0048] In the present invention, the aluminum foil, copper foil and other plain foils need to use plasma to clean the impurities or oxides on the surface of the current collector.
[0049] In the present invention, a DC power supply is used for coating, and the initial vacuum degree of sputtering is 1×10 -6 ~1×10 -4 Pa, preferably, the vacuum degree is 3×10 -6 ~4×10 -5 Pa, further 7×10 -6 ~1×10 -5 Pa.
[0050] In the present invention, the flow rate of argon gas during the sputtering process is 20 to 150 sccm, preferably, the flow rate of argon gas is 50 to 120 sccm, and further preferably, 80 to 110 sccm.
[0051] In the present invention, the sputtering power is 10 to 80 W, preferably, the sputtering power is 20 to 65 W, and further preferably, 25 to 55 W.
[0052] In the present invention, the number of sputtering is 1 to 6 times, preferably 2 to 5 times, and further preferably 2 to 3 times.
[0053] In the present invention, the total magnetron sputtering time is controlled to be 5 to 120 minutes, preferably, the time is 5 to 90 minutes, further 30 to 70 minutes.
[0054] The bismuth negative electrode of the present invention is used for the preparation of sodium ion batteries.
[0055] In the present invention, the bismuth negative electrode of the present invention can be used to prepare a sodium ion battery based on conventional ideas.
[0056] The present invention also provides a button-type battery, which comprises the bismuth negative electrode prepared by magnetron sputtering.
[0057] The structure of the button battery comprises a positive electrode shell, a bismuth negative electrode, a polyethylene diaphragm, a glass fiber diaphragm, a positive electrode, a gasket, a spring, and a negative electrode shell in sequence.
[0058] The button cell of the present invention, in addition to using the bismuth negative electrode of the present invention, other components and structures can be well-known. For example, the sodium sheet, diaphragm, electrolyte and battery structure features can all be conventional.
[0059] For example, the positive electrode of the present invention may include a current collector and a positive electrode material composited on the surface thereof, wherein the positive electrode material includes a conventional sodium-based positive electrode active material, a conductive agent, and a binder.
[0060] For example, the positive electrode active material includes, but is not limited to, sodium vanadium phosphate, sodium vanadium fluoride phosphate, layered oxide positive electrode materials, and Prussian blue and its analog positive electrode and other common positive electrode active materials with practical significance.
[0061] Test conditions
[0062] Preparation of positive electrode sheet: weigh 0.8g of commercial sodium vanadium phosphate (NFPP) positive electrode material and mix with 0.1g of conductive carbon and grind for about 30min, then transfer it into a weighing bottle and drop 2g of PVDF / NMP (N-methylpyrrolidone) solution with a PVDF content of 5%, then add about 1mL of NMP, stir for 12h, and then place the stirred mixture on the carbon-coated aluminum foil as the substrate, use a scraper to scrape it evenly, put it in a vacuum drying oven and dry it at 60℃ for 6h, then dry it at 90℃ for 12h, then take it out and cut it into a positive electrode sheet with a diameter of 12mm, where the ratio of active material, conductive carbon and binder is 8:1:1. The loading amount of positive electrode material is about 14mg cm -2 Preparation of sodium ion battery electrolyte: 16.8 g of sodium hexafluorophosphate (NaPF6) was weighed and dissolved in 100 mL of ethylene glycol dimethyl ether (DME), and 10 g of molecular sieves were added to absorb some of the water that may remain in DME to obtain 1M NaPF6 / DME electrolyte. The battery separator was a 19 mm polyethylene separator and a 19 mm glass fiber separator.
[0063] The half-cell was assembled using sodium sheets, electrolyte, separator and corresponding bismuth negative electrode at a current density of 2A. -2 The cycle stability was tested under 0.1Ag -2 , 0.2Ag-2 , 0.5Ag -2 , 1Ag -2 , 2Ag -2 , 5Ag -2 , 10Ag -2 The current density test rate performance is tested in the voltage range of 0 to 1.5V.
[0064] The positive electrode, electrolyte, separator and corresponding bismuth negative electrode prepared above were used to assemble a full battery to test the cycling stability. The loading amount of the positive electrode material was 14 ± 0.1 mg cm -2 The current density of the test is 2A g -2 The tested voltage range is 1.5 to 3.9 V, and the specific capacity of the positive electrode active material is 100 mAg -1 .
[0065] Example 1
[0066] After installing the bismuth target, place the current collector substrate (commercial carbon-coated aluminum foil in this case) flat on the sample holder, start magnetron sputtering, and wait until the initial vacuum reaches 1×10 -5 Pa, the magnetron sputtering process parameters were adjusted: vacuum DC sputtering power 30W, argon flow rate 100sccm, sputtering times 2 times, each sputtering 23min, total sputtering time 46min, sample holder rotation speed 8r / min. The interval between adjacent sputtering steps was 4-5min, and the pressure of the system during the interval was controlled to 1×10 -5 Pa, metallic bismuth was sputtered onto the carbon-coated aluminum foil, and the loading amount of the bismuth negative electrode was 3±0.2 mg.
[0067] Example 2
[0068] Compared with Example 1, the only difference is that the current collector substrate is changed. The experimental groups are:
[0069] Group A: The current collector substrate is aluminum foil;
[0070] Group B: The current collector substrate is copper foil;
[0071] Other operations and parameters are the same as in Example 1.
[0072] The bismuth negative electrode prepared in Example 1 and Example 2 was tested for the first coulombic efficiency (HCE) of the half-cell, the capacity retention rate (HCR) after 300 cycles, and the capacity retention rate (FCR) of the full battery after 300 cycles according to the test conditions.
[0073] Table 1 The first coulombic efficiency and cycle stability of sodium-ion half-cells and full cells assembled using different current collectors.
[0074] Half-cell Current collector substrate HCE HCR FCR Example 1 Carbon coated aluminum foil 99.8% 96.8% 86.3% Example 2-Group A Aluminum foil 94.3% 72.4% 66.5% Example 2-Group B Copper Foil 95.2% 68.7% 61.9%
[0075] It can be seen from Table 1 that the bismuth negative electrodes prepared using different current collector materials have higher first coulombic efficiency and cycle stability.
[0076] Example 3
[0077] Compared with Example 1, the only difference is that the number of sputtering times or the sputtering power or the total sputtering time is changed, and the sputtering time (min) and the sputtering power (W) are marked as t1, t2, t3... and W1, W2, W3... respectively according to the number of sputtering times. The subsequent examples and comparative examples are consistent with this marking method, and the experimental groups are:
[0078] Group A: Bismuth negative electrode was prepared using different sputtering times N, where the sputtering time was 46 / N min and the sputtering process and other parameters were the same.
[0079] The results of different sputtering times are shown in Table 2;
[0080] Table 2 The first coulombic efficiency and cycle stability of sodium ion half-cells and full cells assembled with bismuth negative electrodes prepared with different sputtering times.
[0081] Sputtering times HCE HCR FCR Example 3-A1 1 89.8% 61.2% 55.9% Example 3-A2 3 97.3% 88.6% 79.8% Example 3-A3 4 94.7% 78.4% 72.5%
[0082] Group B: Bismuth negative electrode was prepared using different sputtering powers.
[0083] The sputtering was performed using a two-stage sputtering process, and other operations and parameters were the same; the results are shown in Table 3;
[0084] Table 3 The first coulombic efficiency and cycle stability of sodium ion half-cells and full cells assembled with bismuth anode prepared with different sputtering powers.
[0085] <![CDATA[W1]]> t1 <![CDATA[W2]]> t2 HCE HCR FCR Example 3-B1 55 16 30 30 83.6% 78.5% 70.4% Example 3-B2 30 30 55 16 80.8% 73.7% 67.2% Example 3-B3 55 23 55 23 75.4% 70.9% 61.3% Example 3-B4 30 23 20 23 99.9% 97.6% 89.5%
[0086] Other operations and parameters are the same as in Example 1.
[0087] Example 4
[0088] This embodiment further illustrates and optimizes the sputtering process parameters based on the embodiment 3. Compared with the embodiment 1, the only difference is that two or three of the sputtering times, the sputtering power and the total sputtering time are changed at the same time, and the other operations and parameters are the same as the embodiment 1.
[0089] Table 4 The first coulombic efficiency and cycle stability of sodium ion half-cells and full cells assembled with bismuth negative electrodes prepared at different sputtering powers with different sputtering times and sputtering times.
[0090] <![CDATA[t1]]> <![CDATA[W1]]> <![CDATA[t2]]> <![CDATA[W2]]> <![CDATA[t3]]> <![CDATA[W3]]> HCE HCR FCR Example 4-Group A 23 30 23 30 13 30 96.7% 87.5% 78.1% Example 4-Group B 23 30 23 30 23 30 95.3% 86.0% 76.6% Example 4-Group C 20 30 20 30 10 30 99.8% 94.2% 86.2%
[0091] It can be seen from Table 2 that when the sputtering times are 2-3 times, the bismuth negative electrode has better performance.
[0092] It can be seen from Table 3 that under the same total sputtering time, the use of a sputtering method with decreasing power can help to further improve the performance of the prepared bismuth negative electrode.
[0093] Comparative Example 1
[0094] Compared with Example 1, the only difference is that the target material used is Sb target or Sn target, and the other operations and parameters are the same as those in Example 1.
[0095] Comparative Example 2
[0096] Commercial bismuth powder electrodes were prepared by a similar doctor blade coating method to the preparation of positive electrode sheets. Commercial bismuth powder (5-20 μm), conductive carbon and PVDF binder were ground and mixed in a weight ratio of 8:1:1. An appropriate amount of NMP was added and magnetically stirred for about 1 hour to form a uniform slurry. The slurry was then coated on carbon-coated aluminum foil. The active material loading was about 3 mg cm -2 , and further vacuum dried at 80°C for 12 h, and the obtained electrode piece was cut into electrode pieces with a diameter of 14 mm to obtain a scraped bismuth negative electrode.
[0097] Comparative Example 3
[0098] The carbon-coated aluminum foil was used as the cathode and the pure bismuth metal was used as the anode, and immersed in the electrolyte. The electrolyte formula was: 8g bismuth nitrate, 3g tartaric acid, 3g polyethylene glycol, 5g NiCl, dissolved in 200mL dimethyl sulfoxide (DMSO). -2 The current density is used to reduce and deposit bismuth on the surface of the carbon-coated aluminum foil to form a bismuth layer, thereby obtaining an electroplated bismuth negative electrode (the bismuth content of the plated electrode is the same as that of Example 1).
[0099] Comparative Example 4
[0100] Compared with Example 1, the only difference is that the sputtering power used in the first sputtering is 100 W, and the other operations and parameters are the same as those in Example 1.
[0101] Comparative Example 5
[0102] Compared with Example 1, the only difference is that the second sputtering time is 80 minutes, and the other operations and parameters are the same as those in Example 1.
[0103] Table 5: Each comparative example is tested for half-cell and full-cell performance according to the test conditions. The test results are as follows:
[0104]
[0105] Figure 1 This is the SEM image of the bismuth negative electrode obtained in Example 1. It can be seen that the bismuth negative electrode obtained by magnetron sputtering has a uniform morphology and a uniform structure. Figure 2The SEM image of the half-cell assembled with the obtained bismuth negative electrode after 100 cycles under the above test conditions shows that the bismuth after the cycle shows obvious fiberization and a regular uniform interface under stress. Compared with the Sn and Sb negative electrodes prepared by magnetron sputtering, the Bi negative electrode shows extremely excellent stability, which shows that it is difficult to deduce the process of preparing Bi negative electrodes through the existing magnetron sputtering process. Therefore, the preparation of Bi-based sodium ion battery negative electrodes through this magnetron sputtering strategy has unique technical advantages.
[0106] Figure 3 and Figure 5 The cycle performance diagrams of the half-cell and full-cell assembled with the bismuth negative electrode prepared by the method described in Example 1 show that the cycle performance is excellent. Figure 6 This is a rate performance diagram of a half-cell assembled with a bismuth negative electrode prepared by the method described in Example 1. The bismuth negative electrode has good rate performance.
Claims
1. A method for preparing a bismuth metal negative electrode, characterized in that: The bismuth metal negative electrode is prepared by sputtering a bismuth metal active layer on a current collector substrate by magnetron sputtering.
2. The method for preparing a bismuth metal negative electrode according to claim 1, characterized in that: The current collector substrate is at least one of current collector aluminum foil, carbon-coated aluminum foil, and copper foil.
3. The method for preparing a bismuth metal negative electrode according to claim 1, characterized in that: The magnetron sputtering stage uses a DC power supply for sputtering; Preferably, the initial vacuum degree of sputtering is 1×10 -6 ~1×10 -4 Pa, preferably, the initial vacuum degree is 3×10 -6 ~4×10 -5 Pa, further 7×10 -6 ~1×10 -5 Pa; Preferably, the argon gas flow rate during the sputtering process is 20 to 150 sccm, preferably, the argon gas flow rate is 50 to 120 sccm, further 80 to 110 sccm; Preferably, the sputtering power is 10 to 80 W, preferably, the sputtering power is 20 to 65 W, and more preferably, 25 to 55 W; Preferably, the total sputtering time is 5 to 120 min, preferably 5 to 90 min, and more preferably 30 to 70 min.
4. The method for preparing a bismuth metal negative electrode according to any one of claims 1 to 3, characterized in that: The sputtering process includes N sputtering processes, wherein adjacent sputtering stages are separated by a time interval of t, and the pressure of the system during the interval is negative pressure; N is 2 to 6; the time t is within 5 minutes; and the time of each sputtering stage is 0.1 to 2 times of the average sputtering time.
5. The method for preparing a bismuth metal negative electrode according to claim 4, characterized in that: The N is 2 to 3; the time t is 1 to 5 minutes; and the time of each sputtering section is 0.5 to 1.5 times of the average sputtering time.
6. The method for preparing a bismuth metal negative electrode according to claim 5, characterized in that: During the N-stage sputtering process, the power of the N-stage sputtering is 0.5 to 1 times the power of the N-1-stage sputtering; Preferably, the time of the Nth sputtering stage is 0.1 to 1 times the time of the N-1th sputtering stage.
7. The method for preparing a bismuth metal negative electrode according to claim 6, characterized in that: The N-stage sputtering process is a two-stage sputtering process, wherein the power of the first stage magnetron sputtering is 25-35W, and the time of the first stage magnetron sputtering is 15-25Min; the power of the second stage magnetron sputtering is 20-30W, and the time of the second stage magnetron sputtering is 15-25Min; further preferably, the power of the first stage magnetron sputtering is 25-35W, and the time of the first stage magnetron sputtering is 20-25Min; the power of the second stage magnetron sputtering is 20-25W, and the time of the second stage magnetron sputtering is 20-25Min; Preferably, the N-stage sputtering process is a three-stage sputtering process, wherein the power of each stage of sputtering can be 25-35W, wherein the sputtering time of the first two stages is 20-25min, and the sputtering time of the last stage is 10-25min.
8. A bismuth metal negative electrode prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a bismuth metal negative electrode prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It is used as the negative electrode in the preparation of sodium ion batteries.
10. A sodium ion battery, comprising a positive electrode, a barrier layer and a negative electrode which are composited in sequence, wherein: The negative electrode is a bismuth metal negative electrode prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Wide-temperature sodium ion battery based on metal bismuth negative electrode
CN113140723A
Bismuth electrode material and preparation method thereof
CN116435495A
Composite current collector with sodium-philic interface, preparation of composite current collector and application of composite current collector in negative-electrode-free sodium battery
CN117747847A
Modified current collector and preparation thereof, and application of modified current collector in negative-electrode-free metal battery
CN118198376A